Association of systemic vitamin D on the course of dengue virus infection in adults: a single-centre dengue cohort study at a large institution in Singapore - Sapna P Sadarangani; Htet Lin Htun; Weiping Ling; Robert Hawkins; Tsin Wen Yeo; Laura Rivino; Paul A MacAry; Yee-Sin Leo (Singapore Medical Journal)
Introduction: Host immune responses may impact dengue severity in adults. Vitamin D has multiple immunomodulatory effects on innate and adaptive immunity. Methods: We evaluated the association between systemic 25-hydroxyvitamin D [25-(OH) D] and dengue disease severity in adults. We measured plasma for total 25-(OH) D levels with an electrochemiluminescence immunoassay using stored samples from participants with laboratory-confirmed dengue, who were prospectively enrolled in 2012–2016 at our institution. Results: A total of 80 participants (median age 43 years) were enrolled in the study. Six participants had severe dengue based on the World Health Organization (WHO) 1997 criteria (i.e. dengue haemorrhagic fever/dengue shock syndrome) and another six had severe dengue based on the WHO 2009 criteria. Median 25-(OH) D at the acute phase of dengue was 6.175 (interquartile range 3.82–8.21, range 3.00–15.29) mcg/L in all participants. The 25-(OH) D showed an inverse linear trend with severe dengue manifestations based on the WHO 2009 criteria (adjusted risk ratio 0.72, 95% confidence interval 0.57–0.91, P < 0.01) after adjustment for age, gender and ethnicity. Conclusion: Limited studies have evaluated the role of systemic 25-(OH) D on dengue severity. Our study found low systemic 25-(OH) D was associated with increased dengue disease severity, particularly for severe bleeding that was not explained by thrombocytopenia. Further studies investigating the underlying immune mechanisms and effects on the vascular endothelium are needed.